The in vitro effect of lactose on Clostridium perfringens alpha toxin production and the implications of lactose consumption for in vivo anti-alpha toxin antibody production - Jill Derix; Richard Ducatelle; Bart Pardon; Evi Croes; Niels Groot Nibbelink; Linda Van Deurzen-Duineveld; Filip Van Immerseel; Evy Goossens (Journal of Dairy Science, 2023)
ABSTRACT: Necro-hemorrhagic enteritis in calves, caused by Clostridium perfringens type A, is a fatal disease, mostly affecting calves in intensive rearing systems. The lack of development of active immunity against α toxin, an essential virulence factor in the pathogenesis, has been proposed as a main trigger. In this experimental study, the effect of a set of milk replacer components on α toxin production, and the effect of lactose on in vivo antibody production, were investigated. For the latter, Holstein-Friesian bull calves (n = 18) were fed an all liquid diet that contained either a milk replacer with high-lactose content (45% DM) or the same milk replacer that was lactase treated, resulting in a lactose-free equivalent. Antibody levels against α toxin were monitored from 2 to 12 wk of age. In the in vitro part of the study, a concentration-dependent inhibitory effect of lactose on in vitro C. perfringens α toxin activity was observed, whereas protein did not influence α toxin activity. The in vivo experiment then showed from the age of 10 wk onwards, that anti-α toxin antibody levels of high-lactose animals declined, whereas antibody levels of the animals consuming lactose-free milk replacer remained the same throughout the trial. This points to a natural decline in maternal immunity of lactose-consuming animals, that is not compensated by the development of an active immunity, resulting in inferior protection. This study suggests that dietary lactose reduces C. perfringens α toxin production in vivo, which may lead to a decreased antigen presentation and thus lower serum antibody levels against the toxin. Consequently, any event causing massive α toxin production puts lactose-consuming calves at higher risk of developing necro-hemorrhagic enteritis.